2020
DOI: 10.1088/1757-899x/928/3/032050
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning with network of Wearable sensors for preventing the Risk of Falls for Older People

Abstract: Activity recognition (AR) systems for older adults are common in residential health care including hospitals or nursing homes; therefore, numerous solutions and studies presented to improve the performance of the AR systems. Yet, delivering sufficiently robust AR systems from sensor data recorded is a challenging task. AR in a smart environment utilizes large amounts of sensor data to derive effective features from the data to track the activity daily living. This paper maximizes the performance of AR system f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The studies [17,19,[86][87][88][89][90][91][92][93][94][95], highlighted DL-based prediction of other age-related other issues such as Type -2 diabetics, COVID-19 in older patients, coronary blockage in arteries, age-related eye diseases, brain age with old age, age-related disease gene associations, and heart stroke. Interesting findings and summary of these studies [17,19,[86][87][88][89][90][91][92][93][94][95] is provided in Tables A5 and A6 in Appendix A.…”
Section: • Prediction Over Spectrum Of Age-related Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies [17,19,[86][87][88][89][90][91][92][93][94][95], highlighted DL-based prediction of other age-related other issues such as Type -2 diabetics, COVID-19 in older patients, coronary blockage in arteries, age-related eye diseases, brain age with old age, age-related disease gene associations, and heart stroke. Interesting findings and summary of these studies [17,19,[86][87][88][89][90][91][92][93][94][95] is provided in Tables A5 and A6 in Appendix A.…”
Section: • Prediction Over Spectrum Of Age-related Issuesmentioning
confidence: 99%
“…The use of genomic data in DL in studying age-related conditions shows promising direction, but domain knowledge is needed to guide the DL model extracting patterns [48]. Some interesting studies have shown the usage of sensor data for guiding and predicting age-related issues [87,88,95]. However, data gathered from sensors may have a certain degree of errors, noise, or redundant information due to battery or communication loss in sensor readings.…”
Section: • Prediction Over Spectrum Of Age-related Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Monitoring and noti cation of abnormal events: Monitoring devices have been proven to ensure the safety of the nursing home residents in fall prevention (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), automatic monitoring of health conditions, and noti cation of emerging events such as heart attacks and fatal accidents (11,12,19,31,. The vital sign of older adults could be collected and recorded by the wearable devices such as clothes and shoes on nursing home residents (35, 95).…”
Section: Function Of Smart Technologies In Nursing Home Settings and Direct Usersmentioning
confidence: 99%